“De Pai pra Filhos”: poder, prestígio e dominação da figura do Pastor-presidente nas relações de sucessão dentro da “Assembleia de Deus Ministério de Madureira”. - FIDALGO, Douglas Alves (2017)
This research analyzes the Assemblies of God in Brazil, focusing on the relations of power, prestige and domination in the succession and family perpetuation of the leaders of this movement in the main positions of "command". We analyze the figure of the Pastor-president and how it became a mechanism of prestige to the point of being legitimized as an unquestionable figure within this institution. We have as a cut for this research the Assemblies of God of the Ministry of Madureira. From the arrival of Bishop Manoel Ferreira to the main command post, it was possible to perceive throughout his administration the family ascent. Children and grandchild occupy the main command posts of the same, a phenomenon not common in the sociocultural construction of this church. The extent to which this relationship concretely influences succession is the guiding question of the research. The bibliographic survey of primary documentation such as newspapers and magazines of the institution was part of the research; And secondary, with the use of "reference books", theses, dissertations and articles that deal directly or correlated with the objectives outlined. In order to accomplish this, a field research was conducted based on interviews with pastors-presidents, former pastors-presidents and pastors of congregation, in order to have a greater comprehension of the material conditions produced by this movement. This research aims to understand the relationship in the present day of perpetuation and family succession in a society that has in democracy and in alternating power the foundations of a society that seeks to avoid the abuses of a group or class of privileged. In the research it was identified that the Pastor-President figure is not a form of "cultural heritage" of colonialism, but rather comes close to patrimonial characteristics, as a response to the traditional needs of the movement that opened the "margin" for the empowerment of a group, Or family, which today forms the foundation of the institution in question. We use as theoretical reference the traditional Weberian ideal type in its patrimonial aspect.